Madhadariye mahephila - Śelata, Himāṃśī (Gūrjara Grantharatna Kāryālaya, 2011)
Collection of letters of a Gujarati author written by Makarand Dave,1922-2005 to Vinoda Meghāṇī, b. 1935, Gujarati author
In Gujarati-Schr
Keywords: Briefsammlung; Dave; Makarand 1922-2005; Authors; Gujarati